An Evaluation of Kenya's Climate Change Policy Challenges for the Building Industry Toward the Realization of Netzero Emissions - Onyalo, Nashon; Tembo, Moffat (International Journal of Computing and Engineering, 2023)
Purpose: Climate change (CC) caused by global warming has become a significant problem today. Although Kenya has established several regulations and policies to deal with the impact of climate change and reduce its nationally determined contribution to near zero as committed in the Paris Agreement, there has been an increase in Co2 emissions, especially from the building industry. Therefore, this research aims to evaluate Kenya's CC legal and regulatory framework, investigate challenges in Kenya's CC regulatory policies, and propose practical strategies for the climate changepolicy challenges for Kenya's building industry to reduce GHG emissions. Methodology: The researcher conducted thorough literature reviews. Secondary qualitative data was collected from government policy documents in various ministries, peer-reviewed papers, international treaties, and working papers from International Non-Governmental Organizations and extensively analyzed using a mixed data analysis strategy. Findings: Results from the analysis revealed that Kenya's CC regulatory framework for the building industry is inadequate, not overarching, and has limited effects on practices and processes in the building industry, thus, the continued increase of GHG emissions. There are no specific industry policies to target their processes and practices, poor implementation and enforcement reduce the effectiveness of the policies, and inadequate funds lead to inept policies and inadequate skills. Unique contribution to theory, practice, and policy: The paper not only contributes Literary Knowledge to the subject area of climate change but also offers policy instruments that can be used as part of NCCAP to assist in CC policy formulation for the building industry.